Ectopic Jejunal Variceal Rupture in a Liver Transplant Recipient Successfully Treated With Percutaneous Transhepatic Coil Embolization: A Case Report. Issue 47 (November 2015) - Abe, Satoru; Akamatsu, Nobuhisa; Hoshikawa, Mayumi; Shirata, Chikara; Sakamoto, Yoshihiro; Hasegawa, Kiyoshi; Kokudo, Norihiro
Abstract : Abstract: Here we present the rupture of ectopic jejunal varices developing in a liver transplant recipient without portal hypertension, which was successfully treated with percutaneous transhepatic coil embolization. A 48-year-old man with massive melena was admitted to our department. He had undergone liver transplantation for hepatitis B virus-related liver cirrhosis 8 months before, and his postoperative course was satisfactory except for an acute cellular rejection. No evidence of bleeding was detected by upper endoscopy or colonoscopy, but dynamic multidetector computed tomography of the whole abdomen revealed an intestinal varix protruding into the lumen of the jejunum with suspected extravasation. There was no evidence of portal venous stenosis or thrombosis. Immediately upon diagnosis of the ruptured ectopic jejunal varix, percutaneous transhepatic coil embolization was performed, achieving complete hemostasis. The portal venous pressure measured during the procedure was within normal limits. He was discharged from the hospital 11 days after embolization and remained in stable condition without re-bleeding 6 months after discharge. This is the first report of an ectopic intestinal variceal rupture in an uneventful liver transplant recipient that was successfully treated with interventional percutaneous transhepatic coil embolization. Clinicians encountering liver transplant recipients with melena should be aware of the possibility of late-onset rupture of ectopic varices, even in those having an uneventful post-transplant course without portal hypertension. Abstract : Supplemental Digital Content is available in the text